A lightweight, low-cost and self-diagnosing mechatronic jaw gripper for the aerial picking with unmanned aerial vehicles - Lieret, Markus; Lukas, Jakob; Nikol, Markus; Franke, Jörg (Procedia Manufacturing, 2020)
Within recent years the gripping and manipulation of individual objects using unmanned aerial vehicles (UAVs) has become an area of broad scientific research as UAVs allow a fast and three-dimensional transportation of the grasped objects. However, currently there are neither standards for aerial gripping devices nor are there grippers available that are both lightweight and robust enough for the usage with drones and can provide the required feedback on whether the gripping process was successful. In this paper, we therefore present a lightweight, low-cost and self-diagnosing mechatronic jaw gripper for the application with autonomous UAVs. The gripper offers an energy-saving design and an integrated measurement system to detect whether an object was successfully grasped. To evaluate the performance of the gripper it is attached to a quadrotor and tested within different scenarios. The tests include the detection of successfully grasped or dropped out objects and the autonomous pickup and deposit.
Keywords: aerial grasping; gripper technologies; autonomous aerial vehicles; object interaction; robotics

Correlation Analysis of Factors Influencing the Motion Planning Accuracy of Articulated Robots - Kedilioglu, Oguz; Nikol, Markus; Walter, Jonas; Franke, Jörg (2023 9th International Conference on Automation, Robotics and Applications (ICARA), 2023)
The motion planning accuracy of articulated robots can be increased by augmenting them with an objective function. Parameters that influence the absolute accuracy of 6-axis articulated robots can be integrated into such objective functions. However, it is still unclear how to prioritize the various influencing factors so that they can be utilized together instead of separately. Here, it is shown how to rate these factors by analyzing and comparing their impact on the accuracy of the robot. The factors manipulability, smoothness, gear backlash caused by direction change of axis rotation, joint space distance and robot layout are studied in this regard. The evaluation with a 6DoF laser tracker reveals that manipulability and smoothness have the biggest impact. With these results it is possible to combine multiple factors into a comprehensive function and achieve a higher accuracy without the necessity of applying any hardware upgrades.<br